A Comparative Analysis on Efficiency of the Student Loan Repayment Policy in Ghana, Kenya, Tanzania, Rwanda and Nigeria - Benjamin, Korankye; Wen, Xuezhou; Baah Nketia, Easmond; Kweitsu, Godson (International Journal of Scientific Research and Management (IJSRM), 2019)
The Ghanaian student loan has been touted as an innovative policy to enhance human development yet the policy is contending with inherent inefficiencies. With the general objective of this study, to critically analyze the success and sustainability of the SLTF loan in Ghana through the repayment and recovery rate using the relative efficiency index (REI=Repayment Ratio / Recovery Ratio) as compare to other Africa countries. This research analyzed the repayment mechanism used in the Ghanaian SLTF and the other countries under study, focusing on a payment schedule, time-frame and the interest rate applied. From the research, although the repayment ratio is high mean, the value of loan amount is also high this suggests that there are gaps to be filled in terms of repayment. Loan repayment is also affected by the interest rate and the salary as shown in the data. The researcher recommends that the loan amount should be reviewed upwards while the repayment period of the student loan remains 10years. With trending issues based on others literature on student loans, the researcher can predict that the loan efficiency would be positive if a high percentage of the loans are paid by student borrowers within the repayment period.